2008
DOI: 10.1007/s10812-008-9097-3
|View full text |Cite
|
Sign up to set email alerts
|

Infrared absorption spectra and structure of TiO2-SiO2 composites

Abstract: The composites xTiO 2 -(1-x)SiO 2 (x = 0.1, 0.5, 0.9) were obtained by coprecipitation from solutions of alkoxides: tetraethoxysilane (TEOS) and titanium tetraisopropoxide (TIPT). Intermolecular interaction of the components of the composite is apparent in the IR absorption spectra in the 928-952 cm -1 region, and is connected with bending vibrations of the Si-O-Ti bond.Introduction. Composites based on titanium and silicon dioxides have begun to be used relatively recently as catalysts and photocatalysts for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(67 citation statements)
references
References 13 publications
5
60
0
2
Order By: Relevance
“…950 cm À1 ) bonds seemed to be perturbed in the T-PEI/silica, possibly because of TiÀO and TiÀN vibrations, which were not present in the A-PEI/silica material. [31,[35][36][37] The presence of the polymer in the hybrid materials could be identified by using the CÀH stretching vibrations that appeared around 2800 to 2900 cm À1 in all PEI-containing materials. [28][29]38] Similarly, the characteristic absorptions observed in the PEI/silica materials at approximately 1460, 1570, and 1650 cm À1 could be attributed to the CÀH bending, secondary amine NÀH bending, and primary amine NÀH bending modes, respectively.…”
mentioning
confidence: 99%
“…950 cm À1 ) bonds seemed to be perturbed in the T-PEI/silica, possibly because of TiÀO and TiÀN vibrations, which were not present in the A-PEI/silica material. [31,[35][36][37] The presence of the polymer in the hybrid materials could be identified by using the CÀH stretching vibrations that appeared around 2800 to 2900 cm À1 in all PEI-containing materials. [28][29]38] Similarly, the characteristic absorptions observed in the PEI/silica materials at approximately 1460, 1570, and 1650 cm À1 could be attributed to the CÀH bending, secondary amine NÀH bending, and primary amine NÀH bending modes, respectively.…”
mentioning
confidence: 99%
“…1) together with the absorption bands characteristic of the individual titania and silica, exhibits the presence of the absorption band in the range of 928-949 cm -1 , which refers to the characteristic vibrations of Si-O-Ti bonds [9]. At the same time, the ''core SiO 2 -shell TiO 2 '' composite in this range does not contain a similar absorption band (curve 2, Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Less studied are the composite materials in the system SiO 2 -TiO 2 , although they are known to exist in several different morphologies: co-precipitated powders, xerogels, mesostructured composite materials with the ''core-shell'' morphology, where each of the components with equal probability can act as the core or the shell [8]. Various methods of obtaining such composite materials are determined not only by the nature of the interaction between different components [9,10], but also by resistance to thermal stress [11], various surface properties, which open new perspectives and possibilities for their practical application [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…And the composition of the flux results in significant changes in the molten structure where the hydrogen can dissolve as a free hydroxyl ion (OH -) or an incorporated hydroxyl (Si-OH). , a weak transmittance band is observed, which has been suggested to be the bending vibration of surface absorbed H2O on SiO2 according to Marashkevich et al 10) No apparent difference was observed with changes in FeO/SiO2 indicating that the surface absorbed H2O is relatively not a factor. At lower wavenumbers of 940 cm -1 , a ridge is observed, which is the hydroxylated silica bending vibration of Si-OH.…”
Section: Understanding the Structure Of Molten Fluxes Andmentioning
confidence: 82%
“…For an acidic oxide slag system, lower FeO/SiO2 or increased SiO2 content increases the bridged oxygen in the network structure, where H2O can dissociate and be incorporated into the silicate structure as Si-OH, which increases the hydrogen solubility. Near 930 cm -1 , studies 10) have shown the existence of a Ti-O-Si bending vibration, but was not pronounced. This may suggest that the hydrogen dissolution is relatively more affected by concentration changes in FeO and SiO2 than the TiO2 additions.…”
Section: Understanding the Structure Of Molten Fluxes Andmentioning
confidence: 91%